2003
DOI: 10.1016/s1389-1723(03)80195-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oxidation-reduction potential and pH as monitoring and control parameters for nitrogen removal in swine wastewater treatment by sequencing batch reactors

Abstract: Two bench-scale sequencing batch reactors (SBRs) were operated in a fixed hydraulic retention time study to investigate the effectiveness of oxidation-reduction potential (ORP), pH and dissolved oxygen as parameters for indicating denitrification followed by nitrification in SBRs for swine wastewater treatment. The ORP and pH profiles were monitored and evaluated under different denitrification and nitrification conditions with and without a supplemental carbon source. With a low C/N ratio, and using a suitabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(30 citation statements)
references
References 15 publications
2
26
0
2
Order By: Relevance
“…Para optimizar el desempeño y mejorar el control del proceso se deben implementar estrategias de control y realizar mediciones de parámetros en tiempo real. Algunos de los más utilizados son el potencial de oxidoreducción (ORP, por sus siglas en inglés), pH y el oxígeno disuelto (OD) [22][23].…”
Section: Junio De 2014unclassified
“…Para optimizar el desempeño y mejorar el control del proceso se deben implementar estrategias de control y realizar mediciones de parámetros en tiempo real. Algunos de los más utilizados son el potencial de oxidoreducción (ORP, por sus siglas en inglés), pH y el oxígeno disuelto (OD) [22][23].…”
Section: Junio De 2014unclassified
“…When the ORP is positive, it means that the oxidation ability of water body is strong, that is the ability of the recursive organism which handles the biological metabolism is strong. If the pH, DO and temperature are suitable, the pollutants in the water will be decomposed fast and effectively [28] . The principle of ORP measurement is similar with the measuring of pH, which based on the selectivity of H + by glass electrode, while the principle of ORP measurement refers to the electrons' acceptance or release of noble metal electrode.…”
Section: Orpmentioning
confidence: 99%
“…Run A1 was operated using a suitable organic load and C/N ratio (approximately 3.1 of BOD 5: TN), while runs A2, B1 and B2 were operated using a low C/N ratio (average BOD/ TN ratio between 1.3 and 1.8) in the influent. The reactor was constructed of Plexiglas and had a working volume of 9 L, as described in our previous papers [21,22]. The reactors had the following five sequences ( Fig.…”
Section: Sequencing Batch Reactors and Operational Strategiesmentioning
confidence: 99%
“…It was found that the use of external carbon sources [20][21][22][23] in the reactor was a viable method of enhancing sequencing batch reactor (SBR) performance. In this study, the relationship between incomplete denitrification caused by a low C/N ratio and sludge foaming was investigated.…”
Section: Introductionmentioning
confidence: 99%